1984
DOI: 10.1007/bf02515500
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering ecology of two social halictine bees, Lasioglossum duplex and L. problematicum

Abstract: SummaryOverwintering of two social halictine bees, Lasioglossum duplex (Dalla Torre) and L. problematicum (Blüthgen), was studied. In L. duplex many females stay near the old nests, each female preparing a hibernaculum separated from the natal nest. In L. problematicum most females overwinter communally within the natal nest. This difference in overwintering habits relates to the social structure in the next spring. L. duplex is nearly always solitary in spring although later becoming eusocial, whereas many ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Those halictines that overwinter away from the natal nest, such as H. rubicundus, exhibit the lowest frequencies of polygynous nest founding (Breed 1976;Kukuk and Decelles 1986;Packer and Knerer 1985). Haplometrosis also occurs in Lasioglossum (Evylaeus) duplex; females overwinter within individual hibernacula beneath the natal nest and independently dig to the surface in the spring, often founding nests within 20 cm of the natal nest (Sakagami et al 1984; similar behavior also indicated for H. ligatus, Packer 1986). This correlation between independent overwintering and independent nest founding (and the converse) suggests that overwintering ecology influences whether pleometrosis or haplometrosis predominates.…”
Section: Population Structurementioning
confidence: 94%
See 1 more Smart Citation
“…Those halictines that overwinter away from the natal nest, such as H. rubicundus, exhibit the lowest frequencies of polygynous nest founding (Breed 1976;Kukuk and Decelles 1986;Packer and Knerer 1985). Haplometrosis also occurs in Lasioglossum (Evylaeus) duplex; females overwinter within individual hibernacula beneath the natal nest and independently dig to the surface in the spring, often founding nests within 20 cm of the natal nest (Sakagami et al 1984; similar behavior also indicated for H. ligatus, Packer 1986). This correlation between independent overwintering and independent nest founding (and the converse) suggests that overwintering ecology influences whether pleometrosis or haplometrosis predominates.…”
Section: Population Structurementioning
confidence: 94%
“…Additionally, details of nest distribution, inter-colony interactions, and genetic relatedness in Lasioglossum (Dialictus) zephyrum clearly suggest philopatry (Kukuk and Decelles 1986;Crozier et al 1987;Kukuk 1989a). To date, however, the only quantitative data on female philopatry in halictids is given by Sakagami et al (1984) for L. (Evylaeus) duplex, which overwinters in its natal nests.…”
Section: Introductionmentioning
confidence: 99%
“…In sweat bees, B1 workers must emerge sufficiently early in the season to help rear a B2 (Hirata & Higashi, 2008;Field et al, 2010). Moreover, smaller B1 offspring with a shorter period of growth might allow more time in the season to produce larger B2 offspring, which probably increases adult B2 female overwintering success (Sakagami et al, 1984;Beekman et al, 1998;Brand & Chapuisat, 2012, but see Weissel et al, 2012).…”
Section: Why Not Saw-tooth Clines?mentioning
confidence: 99%
“…Except for Evylaeus, all collected genera overwinter in the prepupal stage within.nata1 nests (Stephen et al 1969), which may protect the inhabitants from ice inoculation. In the halictine bees, winter is passed by emerged adults either in subterranean natal nests or in other, usually subterranean sites (Sakagami and Michener 1962), probably protected from ice inoculation (Sakagami et al 1984).…”
Section: Chorological and Ecological Notesmentioning
confidence: 99%